2007
DOI: 10.1593/neo.07136
|View full text |Cite
|
Sign up to set email alerts
|

SNS-032 Prevents Tumor Cell-Induced Angiogenesis By Inhibiting Vascular Endothelial Growth Factor

Abstract: Cell proliferation, migration, and capillary network formation of endothelial cells are the fundamental steps for angiogenesis, which involves the formation of new blood vessels. The purpose of this study is to investigate the effect of a novel aminothiazole SNS-032 on these critical steps for in vitro angiogenesis using a coculture system consisting of human umbilical vein endothelial cells (HUVECs) and human glioblastoma cells (U87MG). SNS-032 is a potent selective inhibitor of cyclin-dependent kinases 2, 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Although these cell lines do not reflect the heterogeneity of the AML subgroups, they are informative about many aspects of the responses of AML cells to new agents. 35 Previously SNS-032 has been shown to have cell killing activity in glioblastoma 18 and CLL. 16 In the CLL study SNS-032 activity was found to be selective for CLL cells compared with non-malignant cells and its efficacy was not affected by patient characteristics, p53 status or fludarabine resistance making it potentially useful in refractory AML patients too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these cell lines do not reflect the heterogeneity of the AML subgroups, they are informative about many aspects of the responses of AML cells to new agents. 35 Previously SNS-032 has been shown to have cell killing activity in glioblastoma 18 and CLL. 16 In the CLL study SNS-032 activity was found to be selective for CLL cells compared with non-malignant cells and its efficacy was not affected by patient characteristics, p53 status or fludarabine resistance making it potentially useful in refractory AML patients too.…”
Section: Discussionmentioning
confidence: 99%
“…17 The aim of drugs targeting CDKs is to inhibit cell proliferation, 9 but some of these new agents have also been shown to be potent inducers of apoptosis in cancer cells. 12 New CDK inhibitors, including SNS-032, are more selective and less cytotoxic 17,18 and have been shown to prolong stable disease in solid tumors. 7 In this study, we investigated the in vitro effects of SNS-032 in primary AML blasts and AML cell lines both as a single agent and in combination with cytarabine (Ara-C).…”
Section: Introductionmentioning
confidence: 99%
“…Collection of ACC conditioned medium (CM) was performed as described previously (Ali et al, 2007) with minor modification. In brief, when ACC cells were grown to 70% confluence after overnight incubation, they were starved in serum-deprived DMEM for 12 h to obtain cell synchronization (Zhang and Peng, 2009).…”
Section: Isoliquiritigenin Targets Mtor In Adenoid Cystic Carcinoma 501mentioning
confidence: 99%
“…50 Briefly, C6 cells (2 脳 10 5 cells/500 渭l) cells were seeded to 24-well plate, 24 h later, the culture medium was replaced with fetal bovine serum (FBS)-free medium in the presence of LDM (0.1 nM) and TMZ (300 渭M) alone or combination treatment. After 48 h incubation, 8-渭m-pore size polyethylene tetraphthalate (PET) membrane inserts for 24-well plates (no matrigel coated) were located to the wells.…”
Section: Cell Apoptosis Detection With Annexin V-fitc/pi Double Stainmentioning
confidence: 99%